Coil embolization in 481 ruptured intracranial aneurysms: angiographic and clinical results - Hasan Dinç; M. Halil Öztürk; Ahmet Sarı; Ertuğrul Çakır; Gürkan Gazioğlu; Kayhan Kuzeyli (Diagnostic and Interventional Radiology, 2013)

(untitled)
PURPOSEWe aimed to report our 13-year experience with the embolization of ruptured cerebral aneurysms using detachable coils and postembolization angiographic and clinical results. MATERIALS AND METHODSBetween June 1998 and September 2011, 481 patients with ruptured aneurysms were referred for endovascular treatment with detachable coils at our center. The technical feasibility, procedural complications, morbidity, mortality, and initial angiographic and clinical results were evaluated. RESULTSEndovascular treatment was successful in 95.6% of the patients. Postembolization angiography showed complete occlusion in 63.4%, a neck remnant in 30.8%, and incomplete occlusion in 5.8% of the aneurysms. A total of 331 patients were followed up. The overall angiographic results showed stable occlusion in 234 aneurysms (70.7%) and recurrence in 97 aneurysms (29.3%). During the follow-up period, stable angiographic occlusion was evident in 75% of the small, 61% of the large, and 38.5% of the giant aneurysms. Complications during the coiling procedure occurred in 75 procedures (15.6%). Ischemic complications were observed in 33 procedures (6.9%), and perforation of the aneurysm during the coiling occurred in 12 cases (2.5%). Five (41.7%) of 12 patients who had perforation during coiling died. The overall procedure-related morbidity and mortality were 5.6% and 2%, respectively. During the follow-up period, two patients (0.4%) had early rebleeding. None of the patients showed late rebleeding. In the follow-up, the retreatment rate was 12.6%. CONCLUSIONOur data confirm the feasibility, safety, and efficacy of endovascular coil embolization in patients with ruptured cerebral aneurysms.